Inventors at the service of advertising. Patents for the exhibition of advertisements (1859-1966) - Sánchez-Galán, María Begoña (Revista General de Información y Documentación, 2019)
The invention patents preserved in the patent offices are valuable sources of information that allow us to study the technological development of an industrial field and, at the same time, the historical and sociocultural context that gave birth to those inventions. This article presents the results of a research aimed to identify the records related to advertising registered in the Spanish Historical Archive of Patents and Brands (OEPM). The main purpose of this research is to know the contributions that the inventors made to the field of advertising and, in addition, to gain knowledge about the specific information that can be found in the patent files. As a result, 2658 records related to advertising (registered between 1859 and 1966), have been obtained. A specific database has been designed in order to manage the records and to study them by sectors, formats, years and places of presentation. Ten of those patents have been isolated as a sample used to analyse the content and the documents contained in the patent’s files. The analysis of those files reveals that, in addition to technological information, the patents contain socio-cultural data of interest for the study of the history of advertising in Spain.
Keywords: Patents; Advertising; Inventors; Advertising history; Advertising inventions; Advertising projection; Advertising saturation